GABA‐ρ receptors: distinctive functions and molecular pharmacology. (12th April 2017) - Naffaa, Moawiah M; Hung, Sandy; Chebib, Mary; Johnston, Graham A R; Hanrahan, Jane R
Abstract : The homomeric GABA‐ρ ligand‐gated ion channels (also known as GABAC or GABAA ‐ρ receptors) are similar to heteromeric GABAA receptors in structure, function and mechanism of action. However, their distinctive pharmacological properties and distribution make them of special interest. This review focuses on GABA‐ρ ion channel structure, ligand selectivity toward ρ receptors over heteromeric GABAA receptor sub‐types and selectivity between different homomeric ρ sub‐type receptors. Several GABA analogues show selectivity at homomeric GABA‐ρ receptors over heteromeric GABAA receptors. More recently, some synthetic ligands have been found to show selectivity at receptors formed from one ρ subtype over others. The unique pharmacological profiles of these agents are discussed in this review. The classical binding site of GABA within the orthosteric site of GABA‐ρ homomeric receptors is discussed in detail regarding the loops and residues that constitute the binding site. The ligand‐residue interactions in this classical binding and those of mutant receptors are discussed. The structure and conformations of GABA are discussed in regard to its flexibility and molecular properties. Although the binding mode of GABA is difficult to predict, several interactions between GABA and the receptor assist in predicting its potential conformation and mode of action. The structure–activity relationships of GABA and structurally key ligands at ρ receptors are described and discussed.